2010
DOI: 10.1093/toxsci/kfq294
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Metabolism in the Effect of Valproic Acid on Markers of Cell Viability, Necrosis, and Oxidative Stress in Sandwich-Cultured Rat Hepatocytes

Abstract: Valproic acid (VPA) is a drug known for idiosyncratic hepatotoxicity and is associated with oxidative stress. It is metabolized extensively with at least one pathway leading to reactive metabolites. The primary aim of the present study was to determine whether oxidative metabolites of VPA generated in situ contribute to the toxicity of the parent drug in sandwich-cultured rat hepatocytes. Concentration-response experiments with VPA produced median effective concentration values (mean ± SEM) of 1.1 ± 0.4, 12.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 31 publications
4
36
0
Order By: Relevance
“…The findings of this study, together with the available information regarding the chemical reactivity of VPA-G (Stachulski et al, 2006), lead us to conclude that in situ generated VPA-G does not contribute to the hepatocyte toxicity of VPA. As reported previously, the in situ formation of other reactive metabolites of VPA, such as 4-ene-VPA (Kiang et al, 2010) and (E)-2,4-diene-VPA (Surendradoss et al, 2012), also does not play a role in VPA toxicity. Valproyl-S-acyl CoA is another metabolite of VPA formed by the b-oxidation pathway (Silva et al, 2008).…”
Section: Metabolitesupporting
confidence: 65%
See 1 more Smart Citation
“…The findings of this study, together with the available information regarding the chemical reactivity of VPA-G (Stachulski et al, 2006), lead us to conclude that in situ generated VPA-G does not contribute to the hepatocyte toxicity of VPA. As reported previously, the in situ formation of other reactive metabolites of VPA, such as 4-ene-VPA (Kiang et al, 2010) and (E)-2,4-diene-VPA (Surendradoss et al, 2012), also does not play a role in VPA toxicity. Valproyl-S-acyl CoA is another metabolite of VPA formed by the b-oxidation pathway (Silva et al, 2008).…”
Section: Metabolitesupporting
confidence: 65%
“…Other than glucuronidation, pretreatment of rat hepatocytes with b-naphthoflavone also increased cytochrome P450-mediated biotransformation of VPA, as shown in the present study. However, the in situ formation of these VPA oxidative metabolites has been reported not to influence VPA toxicity in sandwich-cultured rat hepatocytes (Kiang et al, 2010;Surendradoss et al, 2012). In the case of diclofenac, the hepatocyte toxicity of this drug has been attributed to the formation of cytochrome P450-mediated oxidative metabolites of diclofenac (Kretz-Rommel and Boelsterli, 1993).…”
Section: Metabolitementioning
confidence: 99%
“…The mechanism of VPA-induced hepatotoxicity is still not completely clear. In vitro and in vivo evidences have suggested that oxidative stress played a critical role in the pathogenesis of VPA-induced hepatotoxicity (Kiang et al, 2010;Tong et al, 2005a,b). It is indicated that excessive production of free radicals and depletion of antioxidants due to oxidative stress are implicated in VPA-induced liver dysfunction (Kiang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…VPA toxicity is associated with increased reactive oxygen species (ROS) formation, which in turn constitutes an important risk factor for tissue damage and organ dysfunction (Fourcade et al, 2010). Several studies have reported the implication of an increased generation of free radicals and oxidative stress in the toxicity induction mechanism of VPA (Kiang et al, 2010;Zhang et al, 2010). Different mechanisms have been proposed to explain inhibition of mitochondrial function by VPA (Tong et al, 2005b;Chang and Abbott, 2006).…”
Section: Introductionmentioning
confidence: 99%